Service In Talun Village Sumedang Regency - Paroli Paroli (UNIVERSITAS PAKUAN, 2023)
Talun Sub-District, Sumedang Regency, is one of the sub-districts in the Sumedang bank district in Sumedang, this research was caused by unsatisfactory service. Based on this, this study aims to determine services and efforts to overcome service problems in the Talun Village, Sumedang Regency. This study uses a qualitative research method approach with the research variable being service. The sampling technique was carried out by purposive sampling technique. The research informants were: Lurah, civil servants and the Talun Village Community, Sumedang Regency. Research data were analyzed using the Miles and Huberman model with steps including data reduction, data presentation, drawing conclusions. The results showed that services in the Talun Village, Sumedang Regency, that the dimensions of physical evidence (tangibles), facilities and infrastructure were equipped again, toilet facilities were added, the dimensions of reliability (reliability), technical services were quite fast, dimensions of responsiveness (responsiveness), in dealing with complaints from the public, has been reduced by the addition of employees, dimensions of assurance or certainty (assurance), employees greet and ask the needs of every member of the public who comes by showing good manners, and dimensions of empathy (emphaty), the attention and care of employees given to the community optimally by giving a smile and greeting directly to the community according to the applicable SOP. For the Talun Village, Sumedang Regency, to be able to carry out the determination of service principles as a whole in accordance with the capabilities and seating of existing facilities, considering that the determination of service principles is very helpful in achieving service goals.